Onset of primary moult in immature and breeding adult Common Swifts Apus apus - Boano G.; Casola D.; Cucco M.; Ferri Mauro; Micheloni P.; Manica M.; Pellegrino I. (Ringing & Migration, 2022)
We studied the primary moult of immature and adult breeding Common Swift Apus apus in Italy. Birds were sampled at breeding colonies, or by attracting them to mist nets with the playback of recorded calls. Our sample of 590 immatures (2cy) assessed that about a quarter (25.6%) of these birds start moulting the inner primaries during their stay in Europe. We find that this moult starts usually in the second half of June, earlier than was observed in other European countries, where individuals begin moulting in July. Interestingly, and in contrast to previous knowledge on the moulting schedules of breeding Common Swifts, we found that more than half of breeding adults (56%, 15 of 27) started their primary moult in July. Moult before the swifts left our study area was limited to the first two inner primaries. Our study showed that breeding Commons Swifts are able to regulate their moult when already engaged in rearing young, and both immature and adult Swifts start their moult before leaving Europe towards their African winter quarters.